Cyanobacterial Diversity and Physicochemical Characteristics of Thermal Springs in The Kütahya Province of Turkey - ÖZtürk Sevi̇lay (Bangladesh Journal of Plant Taxonomy, 2021)
Thermal springs are very difficult environments for organisms due to the high temperature, and physicochemical parameters. Cyanobacteria, which are photosynthetic prokaryotes, are best adapted to these environments. Kütahya is an important thermal area in Turkey. The aim of the study was to determine the cyanobacterial flora with a morphologic and ecologic approach in the 11 thermal. The physicochemical properties of the thermal springs in Kütahya province were measured. The thermal springs are alkaline (pH6) with an average temperature of 52°C. As a result, 54 cyanobacteria taxa were identified. Oscillatoriales were the predominant order in terms of taxa diversity (24 taxa) and biomass size. Statistical analyses were conducted to reveal the physicochemical properties of the thermal springs and the distribution of cyanobacteria in detail. According to these analyses, the thermal springs were classified into two main groups with a Piper. As a result of the RDA analysis under CANOCO 5.0, the total variation was 55.45455, and the first two axes explained a total of 57.43% of the variance. There was a significant difference (P0.001) in the comparison of the physicochemical parameters including pH, EC, TDS, and temperature values of the thermal springs in the Kruskal Wallis tests. Bangladesh J. Plant Taxon. 28(2): 413-428, 2021 (December)